Quantitative Assessment of Knee Effusion‐Synovitis in Older Adults: Association With Knee Structural Abnormalities. Issue 4 (April 2016) - Wang, Xia; Blizzard, Leigh; Jin, Xingzhong; Chen, Zhongshan; Zhu, Zhaohua; Han, Weiyu; Halliday, Andrew; Cicuttini, Flavia; Jones, Graeme; Ding, Changhai
Abstract : Objective: To describe the natural history of quantitatively measured knee effusion‐synovitis and the longitudinal associations between effusion‐synovitis and knee structural factors, including cartilage defects, cartilage volume, subchondral bone marrow lesions, and meniscal pathology, in older adults. Methods: A total of 406 subjects (with a mean age of 63 years, 50% women) were randomly selected at baseline and followed up 2.7 years later. T2‐ or T1‐weighted fat saturation magnetic resonance imaging was used to assess knee effusion‐synovitis maximal area, cartilage defects, cartilage volume, bone marrow lesions, and meniscal pathology at baseline and follow‐up. Multivariable generalized linear regression was performed to analyze the associations between the maximal area of effusion‐synovitis and other joint structural factors after adjustment for age, sex, body mass index, tibial bone area, and/or radiographic osteoarthritis (OA). Results: Over 2.7 years of follow‐up, the size of effusion‐synovitis increased in 29%, remained stable in 50%, and decreased in 22% of the participants. Baseline effusion‐synovitis maximal area was significantly associated with changes in knee cartilage defects (β = 0.18 [95% confidence interval (95% CI)] 0.07, 0.29), bone marrow lesions (β = 0.17 [95% CI 0.05, 0.30]), and cartilage volume (β = −0.40 [95% CI −0.71, −0.09]) but not with change in meniscal pathology. In contrast, baseline structural measures were not associated with change or increase in effusion‐synovitis maximal area. Conclusion: Our findings indicate that knee effusion‐synovitis is not static in older adults. It is predictive of, but not predicted by, other structural abnormalities, suggesting a potential role in early knee OA changes.